Role of prolyl hydroxylase domain proteins in the regulation of insulin secretion. Issue 5 (20th March 2016) - Huang, Mei; Paglialunga, Sabina; Wong, Julia M.‐K.; Hoang, Monica; Pillai, Renjitha; Joseph, Jamie W.
Abstract: Type 2 diabetes is associated with impaired nutrient‐regulated anaplerosis and insulin secretion in pancreatic β ‐cells. One key anaplerotic substrate that may be involved in regulating insulin release is α ‐ketoglutarate ( α KG). Since prolyl hydroxylase domain proteins (PHDs) can metabolize cytosolic α KG, we sought to explore the role of this enzyme in the regulation of β ‐cell function. The oxygen‐sensing PHDs regulate the stability of hypoxia‐inducible factor 1 α (HIF1 α ) as well as other proline‐containing proteins by catalyzing the hydroxylation of proline residues. This reaction is dependent on sufficient levels of oxygen, iron, and α KG. In the present study, we utilized both pharmacological and genetic approaches to assess the impact of inhibiting PHD activity on β ‐cell function. We demonstrate that ethyl‐3, 4‐dihydroxybenzoate (EDHB), a PHD inhibitor, significantly blunted glucose‐stimulated insulin secretion (GSIS) from 832/13 clonal cells, rat, and human islets. EDHB reduced glucose utilization, ATP/ADP ratio, and key TCA cycle intermediates such as pyruvate, citrate, fumarate, and malate. siRNA‐mediated knockdown of PHD1 and PHD3 inhibited GSIS, whereas siRNA‐mediated knockdown of PHD2 had no effect on GSIS. Taken together, the current results demonstrate an important role for PHDs as mediators of islet insulin secretion. Abstract : Prolyl hydroxylase domain (PHD) proteins may play an essential role in the regulation of insulin secretion. Pharmacological targeting and β ‐cell knockdown of PHD3 impaired glucose‐stimulated insulin secretion, suggesting that PHD3 may play a key role in regulating insulin secretion from pancreatic β ‐cells.